Dynamics and Optimal Feet Force Distributions of a Realistic Four-legged Robot - Saurav Agarwal; Abhijit Mahapatra; Shibendu Shekhar Roy (IAES International Journal of Robotics and Automation (IJRA), 2012)
This paper presents a detailed dynamic modeling of realistic four-legged robot. The direct and inverse kinematic analysis for each leg has been considered in order to develop an overall kinematic model of the robot, when it follows a straight path. This study also aims to estimate optimal feet force distributions of the said robot, which is necessary for its real-time control. Three different approaches namely, minimization of norm of feet forces (approach 1), minimization of norm of joint torques (approach 2) and minimization of norm of joint power (approach 3) have been developed. Simulation result shows that approach 3 is more energy efficient foot force formulation than other two approaches. Lagrange-Euler formulation has been utilized to determine the joint torques. The developed dynamic models have been examined through computer simulation of continuous gait of the four-legged robot.DOI: http://dx.doi.org/10.11591/ijra.v1i4.762